Potentially avoidable blood transfusion during trauma resuscitation. Issue 1 (January 2015) - Mitra, Biswadev; Nash, Jessica L.; Cameron, Peter A.; Fitzgerald, Mark C.; Moloney, John; Velmahos, George C.
Abstract: Introduction: Red blood cell (RBC) transfusion is often essential during trauma resuscitation but is associated with high cost and potential adverse outcomes. This study aimed to determine the incidence of potentially avoidable RBC transfusions (PAT) among adult major trauma patients. Materials and methods: A retrospective review of data collected by Registry on patients presenting between Jan 2006 and Dec 2011 was conducted. Eligible patients received at least 1 unit of RBC in the first 24 h following presentation to the Emergency Department (ED). Episodes of PAT were determined according to haemodynamic stability and post-transfusion haemoglobin levels. Results: There were 621 patients included, of whom 224 (36.1%; 95% CI: 32.3–40.0) received PAT. Of them, 132 (58.9%) were haemodynamically stable on arrival and did not require a surgical procedure. Patients with PAT had significantly lower injury severity scores (30 vs 34, p  < 0.01), higher presenting systolic blood pressure (129 vs 112 mm Hg, p  < 0.01) and a lower frequency of a shock index ≥1 (24.1 vs 65.0%, p  < 0.01), compared to those without PAT. They also had a significantly lower mortality (13.4 vs 21.7%, p  < 0.01). Conclusions: PAT after trauma was common and often delivered to haemodynamically stable patients who did not require surgical procedures. Clinical decision pathways for trauma resuscitation should aim to limit PAT.